Organizational factors affecting the performance development of police officers of the rank of non-commissioned officer in provincial police stations in Pathum Thani Province - Wansiripak, Aekniruj; Potivichayanont, Kanjana; Nakaumka, Neeranuch (Journal of MCU Phetchaburi Review, 2026)
The objectives of this research are 1) Study to investigate the level of performance development of non-commissioned police officers; and 2) study to examine the influence of organizational factors on the performance development of non-commissioned police officers. A questionnaire was used to collect data from 328 non-commissioned police officers stationed at police stations in Pathum Thani Province. The statistical methods used include frequency, percentage, standard deviation, and multiple regression analysis. The research findings revealed that 1) motivation for work performance and the development of work competencies, both overall and in each aspect, were at a high level, and 2) Motivational factors related to work performance, including job achievement, recognition, job characteristics, responsibility, career advancement, salary, growth opportunities, and policies and management, all influence the development of work performance among lower-ranking police officers. These eight variables can predict 75.90% of the variance in the development of work performance among lower-ranking police officers. This research provides senior management with information to guide the formulation of policies for developing personnel competencies to achieve maximum organizational efficiency.